COMPARISON OF HEART HATE IN TREADMILL MAXIMUM EFFORT TEST AND HEART HATE EQUATIONS IN PHYSICAL EDUCATION STUDENTS OF UNIVERSIDADE ESTACIO DE SÁ (Fiep Bulletin - online, 2013)
Apparently easy of being measured, the use of the Heart Hate was popularized as a tool for knowing the intensity zone training. But everybody knows that use the correct % of heart hate for practices the activity becomes necessary for we can optimizes the training with a correct control and minimizes the risks of some sort of accident. OBJECTIVE: The objective study it was to compare the reply of the Heart Hate in Maximum effort test in treadmill and compare with 3 regression equations for prediction of the maximum Heart Hate. METHODOLOGY: The present study it is descriptive type research with comparative character. It was chosen 37 individuals healthful with 27,49 ± 6,77 years average age. The 3 regression equations for prediction of the maximum Heart Hat used in the study had been” Karvonen”, Tanaka and Inbar, all equations for healthful masculine individuals. RESULTS: Test = 188,27 bpm; 220 - idade= 192,51*bpm; Imbar= 186,97 bpm and Tanaka= 187,76 bpm. CONCLUSION: Can be observed that was significant difference (p